2019
DOI: 10.1038/s41598-018-36461-6
|View full text |Cite
|
Sign up to set email alerts
|

The neurotoxic secreted phospholipase A2 from the Vipera a. ammodytes venom targets cytochrome c oxidase in neuronal mitochondria

Abstract: The β-neurotoxic secreted phospholipases A2 (sPLA2s) block neuro-muscular transmission by poisoning nerve terminals. Damage inflicted by such sPLA2s (β-ntx) on neuronal mitochondria is characteristic, very similar to that induced by structurally homologous endogenous group IIA sPLA2 when its activity is elevated, as, for example, in the early phase of Alzheimer’s disease. Using ammodytoxin (Atx), the β-ntx from the venom of the nose-horned viper (Vipera a. ammodytes), the sPLA2 receptor R25 has been detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 53 publications
4
19
0
1
Order By: Relevance
“…The structural diversity of sPLA 2 -BPs is consistent with the wide range of pathophysiological activities that have been associated with sPLA 2 s. By binding to sPLA 2 -BPs, sPLA 2 s have been suggested to be involved in inflammation [64,65], hormone release [66,67], neurotoxicity [20,37,68,69] and myotoxicity [22]. It has already been confirmed that sPLA 2 s are ligands for specific sPLA 2 -BPs in cytokine production [70], cell proliferation [71][72][73], cell migration [74], lipid mediator production [75], antibacterial activity [73] and blood coagulation [40].…”
Section: Pathophysiological Significance Of Spla 2 Binding To Spla 2 -Bpssupporting
confidence: 55%
See 2 more Smart Citations
“…The structural diversity of sPLA 2 -BPs is consistent with the wide range of pathophysiological activities that have been associated with sPLA 2 s. By binding to sPLA 2 -BPs, sPLA 2 s have been suggested to be involved in inflammation [64,65], hormone release [66,67], neurotoxicity [20,37,68,69] and myotoxicity [22]. It has already been confirmed that sPLA 2 s are ligands for specific sPLA 2 -BPs in cytokine production [70], cell proliferation [71][72][73], cell migration [74], lipid mediator production [75], antibacterial activity [73] and blood coagulation [40].…”
Section: Pathophysiological Significance Of Spla 2 Binding To Spla 2 -Bpssupporting
confidence: 55%
“…(2) heparan sulphate proteoglycans (HSPGs); (3) integrins; (4) vascular endothelial growth factor receptors (VEGFRs); and (5) ion channels. Two new integral membrane sPLA 2 -BPs have been described recently, a G-protein-coupled receptor (GPCR), and cytochrome c oxidase (CCOX) [35,37]. CCOX is the only known intracellular membrane sPLA 2 -BP, as all of the other integral membrane sPLA 2 -BPs are located in the plasma membrane.…”
Section: Spla 2 S Bind Very Structurally Diverse Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this hypothesis, tetrameric or dimeric configurations may play an important role in neurotoxicity or other functions of human inflammatory sPLA 2 GIIA. Moreover, in pathological conditions, where high concentrations of sPLA 2 have been detected [ 41 , 42 , 43 ], formation of sPLA 2 oligomers could be expected. Additional in vivo studies are needed to explain the role of oligomerization of sPLA 2 in pathophysiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…We searched the SLiMs present in the ELM resource [24] and conserved in the different groups of sPLA2s. We selected for the search "all cellular compartments" because sPLA2s are internalized in cells, and were observed to localize in different cellular organelles, in vesicles in the cytoplasm, in mitochondria, and in the nucleus [26][27][28][29][30]. Of all the motifs identified (Table S1A,B, Supplementary Material), we selected those conserved in toxins but not in mammalian PLA2s, or vice versa.…”
Section: Slims Conserved In Toxins and Not In Mammalian Pla2s Or Vice Versamentioning
confidence: 99%